ACMEOLOGICAL FEATURES OF SUCCESSFUL ENTREPRENEUR - Zoya G. Khanova (Advanced Engineering Research, 2011)
Some psychological problems of the entrepreneurship are considered. Psychological features of an entrepreneur that can lead one to success (initiativity, positive attitude to other people, leadership, responsibility, managerial capabilities, resolution in actions, persistence) are analyzed.